Activity of Meropenem-Vaborbactam in Mouse Models of Infection Due to KPC-Producing Carbapenem-Resistant Enterobacteriaceae - Sabet, Mojgan (Antimicrob Agents Chemother, 2017)
Meropenem-vaborbactam (Vabomere) is highly active against Gram-negative pathogens, especially Klebsiella pneumoniae carbapenemase (KPC)-producing, carbapenem-resistant Enterobacteriaceae. The objective of these studies was to evaluate the efficacy of meropenem alone and in combination with vaborbactam in mouse thigh and lung infection models. Thighs or lungs of neutropenic mice were infected with KPC-producing carbapenem-resistant Enterobacteriaceae, with meropenem MICs ranging from ≤0.06 to 8 mg/liter in the presence of 8 mg/liter vaborbactam. Mice were treated with meropenem alone or meropenem in combination with vaborbactam every 2 h for 24 h to provide exposures comparable to 2-g doses of each component in humans. Meropenem administered in combination with vaborbactam produced bacterial killing in all strains tested, while treatment with meropenem alone either produced less than 0.5 log CFU/tissue of bacterial killing or none at all. In the thigh model, 11 strains were treated with the combination of meropenem plus vaborbactam (300 plus 50 mg/kg of body weight). This combination produced from 0.8 to 2.89 logs of bacterial killing compared to untreated controls at the start of treatment. In the lung infection model, two strains were treated with the same dosage regimen of meropenem and vaborbactam. The combination produced more than 1.83 logs of bacterial killing against both strains tested compared to untreated controls at the start of treatment. Overall, these data suggest that meropenem-vaborbactam may have utility in the treatment of infections due to KPC-producing carbapenem-resistant Enterobacteriaceae.